Genes Linking Copper Trafficking and Homeostasis to the Biogenesis and Activity of the cbb3-Type Cytochrome c Oxidase in the Enteric Pathogen Campylobacter jejuni - Garg, Nitanshu; Taylor, Aidan J.; Pastorelli, Federica; Flannery, Sarah E.; Jackson, Phillip J.; Johnson, Matthew P.; Kelly, David J. (Frontiers in Microbiology, 2021)
Bacterial C-type haem-copper oxidases in the cbb3 family are widespread in microaerophiles, which exploit their high oxygen-binding affinity for growth in microoxic niches. In microaerophilic pathogens, C-type oxidases can be essential for infection, yet little is known about their biogenesis compared to model bacteria. Here, we have identified genes involved in cbb3-oxidase (Cco) assembly and activity in the Gram-negative pathogen Campylobacter jejuni, the commonest cause of human food-borne bacterial gastroenteritis. Several genes of unknown function downstream of the oxidase structural genes ccoNOQP were shown to be essential (cj1483c, cj1486c) or important (cj1484c, cj1485c) for Cco activity; Cj1483 is a CcoH homologue, but surprisingly Cj1484 (designated CcoZ) has structural similarity to MSMEG_4692, involved in Qcr-oxidase supercomplex formation in Mycobacterium smegmatis. Blue-native polyacrylamide gel electrophoresis of detergent solubilised membranes revealed three major bands, one of which contained CcoZ along with Qcr and oxidase subunits. Deletion of putative copper trafficking genes ccoI (cj1155c) and ccoS (cj1154c) abolished Cco activity, which was partially restored by addition of copper during growth, while inactivation of cj0369c encoding a CcoG homologue led to a partial reduction in Cco activity. Deletion of an operon encoding PCuAC (Cj0909) and Sco (Cj0911) periplasmic copper chaperone homologues reduced Cco activity, which was partially restored in the cj0911 mutant by exogenous copper. Phenotypic analyses of gene deletions in the cj1161c-1166c cluster, encoding several genes involved in intracellular metal homeostasis, showed that inactivation of cj1161c (copA), or cj1162c (copZ) led to both elevated intracellular Cu and reduced Cco activity, effects exacerbated at high external Cu. Our work has therefore identified (i) additional Cco subunits, (ii) a previously uncharacterized set of genes linking copper trafficking and Cco activity and (iii) connections with Cu homeostasis in this important pathogen.